Web Technologies and Applications 18th Asia-Pacific Web Conference, APWeb 2016, Suzhou, China, September 23-25, 2016. Proceedings, Part II - Li, Feifei; Shim, Kyuseok; Zheng, Kai; Liu, Guanfeng (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
This LNCS double volume LNCS 9931-9932 constitutes the refereed proceedings of the 18th Asia-Pacific Conference APWeb 2016 held in Suzhou, China, in September 2016. The 79 full papers and presented together with 24 short papers and 17 demo papers were carefully reviewed and selected from 215 submissions. the focus of the conference was on following subjects: Spatio-temporal, Textual and Multimedia Data Management Social Media Data Analysis Modelling and Learning with Big Data Streaming and Real-time Data Analysis Recommendation System Data Quality and Privacy Query Optimization and Scalable Data Processing.